(untitled) (Communications in Computational Physics, 2020)
A hybrid finite element (FEM) and Fourier transform method is implemented to analyze the time domain scattering of a plane wave incident on a 2-D overfilled cavity embedded in the infinite ground plane. The algorithm first removes the time variable by Fourier transform, through which a frequency domain problem is obtained. An artificial boundary condition is then introduced on a hemisphere enclosing the cavity that couples the fields from the infinite exterior domain to those inside. The exterior problem is solved analytically via Fourier series solutions, while the interior region is solved using finite element method. In the end, the image functions in frequency domain are numerically inverted into the time domain. The perfect link over the artificial boundary between the FEM approximation in the interior and analytical solution in the exterior indicates the reliability of the method. A convergence analysis is also performed.